Prevalence estimation of celiac disease in the general adult population of Latvia using serology and HLA genotyping. Issue 2 (1st April 2015) - Leja, Marcis; Shums, Zakera; Nikitina-Zake, Liene; Gavars, Mikus; Kikuste, Ilze; Milo, Jay; Daugule, Ilva; Pahomova, Jelena; Pirags, Valdis; Dzerve, Vilnis; Klovins, Janis; Erglis, Andrejs; et al.
Abstract : Background: Prevalence estimates for celiac disease (CD) depend on the method used. The role of deamidated gliadin peptide (DGP) and genetic testing in epidemiological studies and diagnostic settings of celiac disease (CD) has still to be established. Objectives: The objective of this article is to assess the prevalence of CD in Latvia by combining serological tests with DQ2.5/DQ8 testing. Methods: A total of 1444 adults from a randomly selected cross‐sectional general population sample were tested by ELISA for tTG IgA, DGP IgA and IgG antibodies (QUANTA Lite®, Inova Diagnostics Inc). Samples with tTG IgA ≥20U were tested for EMA IgA by indirect immunofluorescence assay, and all specimens with tTG IgA ≥15U were tested by QUANTA‐Flash® chemiluminescent assays (CIA) (Inova Diagnostics Inc) for tTG IgA, DGP IgA and IgG. DQ2.5/8 was detected in individuals with any positive ELISA test and a subgroup of controls. Results: Forty‐three individuals (2.98%; 95% CI: 2.10–3.86%) tested positive by at least one ELISA test; 41.86% of the serology‐positive individuals (any test above the cutoff) were DQ positive. Six individuals (0.42%; 95% CI: 0.09–0.75%) were triple ELISA positive, and DQ2.5 or DQ8 was positive in all; 0.35% (95% CI: 0.05–0.65%) were tTG IgA and EMA positive. Two tTG IgA‐negative cases were both DGP IgG and IgA positive, both being DQ positive; including them in the "serology‐positive" group would increase the prevalence to 0.49% (95% CI: 0.13–0.85%). CIA tests revealed 2 tTG IgA‐positive and EMA‐negative cases with a positive genotype. DQ2.5 or DQ8 genotype was positive in 28.6% of the serology‐negative population. Conclusions: Estimates of the prevalence of CD in Latvia based on the serogenetic testing approach range from 0.35% to 0.49% depending on the criteria used. There is a rationale for combining serological tests and DQ2.5/8 genotyping.